2013
DOI: 10.9738/cc159.1
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Indocyanine Green Angiography for Evaluation of Blood Supply in a Reconstructed Gastric Tube During Esophagectomy

Abstract: We report a case of necrosis of a reconstructed gastric tube in a 77-year-old male patient who had undergone esophagectomy. At the time of admission, the patient had active gastric ulcers, but these were resolved by treatment with a proton pump inhibitor. Subtotal esophagectomy with gastric tube reconstruction was performed. Visually, the reconstructed gastric tube appeared to be well perfused with blood. Using indocyanine green (ICG) fluorescence imaging the gastroepiploic vessels were well enhanced and no en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…However, these methods cannot provide accurate assessments of the risk of post‐operative splenic ischemia. However, FVI‐ICG that has been used for lymphography, angiography and sentinel lymph node detection can facilitate the real‐time visualization of vascular tissue itself . Therefore, using FVI‐ICG to evaluate splenic blood perfusion after SPDP‐W is quite rational.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these methods cannot provide accurate assessments of the risk of post‐operative splenic ischemia. However, FVI‐ICG that has been used for lymphography, angiography and sentinel lymph node detection can facilitate the real‐time visualization of vascular tissue itself . Therefore, using FVI‐ICG to evaluate splenic blood perfusion after SPDP‐W is quite rational.…”
Section: Discussionmentioning
confidence: 99%
“…However, FVI-ICG that has been used for lymphography, angiography and sentinel lymph node detection can facilitate the real-time visualization of vascular tissue itself. [11][12][13][14][15][16][17][18][19][20] Therefore, using FVI- ICG to evaluate splenic blood perfusion after SPDP-W is quite rational.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, absolute quantification of blood flow is not possible and preliminary data are controversial ( Fig. 9; [103][104][105][106][107][108][109][110]).…”
Section: Visualization Of the Gastric Tube's Perfusionmentioning
confidence: 99%
“…Several reported studies have assessed blood flow in the reconstructed gastric tube using laser Doppler flowmetry [8][9][10][11] or indocyanine green (ICG) fluorescence angiography. [12][13][14][15][16] We previously investigated in detail the hemodynamics of the reconstructed gastric tube using ICG fluorescence angiography 12 and concluded that the time between initial ICG enhancement of the root of the right gastroepiploic artery and enhancement at the tip of the gastric tube was a useful parameter for assessment of blood flow to the gastric tube. In addition, we proposed that the gastric tube was divisible into 3 zones according to the dominant arteries present in the greater curvature: zone 1, the area dominated by the right gastroepiploic vessels; zone 2, the area dominated by the left gastro-epiploic vessels (in all cases, the left gastro-epiploic artery being enhanced in a direction opposite to that of physiologic blood flow); and zone 3, the area initially perfused by short gastric vessels (we usually perform esophago-gastrostomy in this zone; Fig.…”
mentioning
confidence: 99%